The art of the (im)possible: legislators' experiences of the lawmaking process when reforming migration law. (2nd January 2016) - Hedlund, Daniel; Cederborg, Ann-Christin; Zamboni, Mauro
ABSTRACT: We do not know enough about how legislators from different political parties make sense of their ambitions and experiences in relation to the development of asylum policy. In this study we wanted to find out how political discussions can create conditions for legislative change. The current study therefore explored how the Swedish 2005 Aliens Act and the new system for appeals and procedures (NSAP) were negotiated and perceived by 15 legislators of the parliamentary Committee on Social Insurance (COSI) that considered this legal framework that has been effective since 2006. The participants were openly interviewed about their experiences of negotiating migration policy via their committee work. The study is inspired by interpretative phenomenological analysis (IPA) as it can reach an understanding of how research participants' attempt to make sense of their lived experience. First, the interview transcripts were transcribed verbatim and then independently coded by the first two authors. Thereafter, they collaboratively refined the themes and sub-themes and discussed them with the third author. The overall finding is that the preceding political negotiations can be one of the reasons for unclear aims when politicians' propose new legislation. This is because directives can consist of many divergent perspectives and considerations. The specific findings are that the period under consideration was described as dramatic and stressful with the presence of uncommon political collaboration between political parties as well as the pushing of legislation via budget negotiations. In addition, the participants said that the suggested changes in asylum policy and implementation were mainly based on other policy aspects, such as fiscal considerations and state-municipality relations. Participants also viewed that identified problems with asylum decision-making have not been sufficiently resolved by the new framework. Even though this study was conducted in Sweden, its findings can be relevant to other political systems in more developed countries as these states can also struggle with contradictory aims with asylum policy.